Peran Self-Regulated Learning sebagai Mediator dalam Hubungan Gaya Belajar Generasi Z, Artificial Intelligence, dan Literasi Keuangan Digital terhadap Literasi Ekonomi Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Nusantara Pgri Kediri - Sumargo, Oktya Anggarani (Jurnal Ragam Pengabdian, 2026)
Digital transformation in the Society 5.0 era has changed students’ learning patterns, especially Generation Z, who are visual, interactive, flexible, and technology-oriented. This study aims to analyze the role of Self-Regulated Learning (SRL) as a mediator between Generation Z learning styles, Artificial Intelligence (AI) utilization, digital financial literacy, and students’ economic literacy at the Faculty of Economics and Business, Universitas Nusantara PGRI Kediri. Using a quantitative explanatory approach, data from 357 respondents were analyzed through SEM-PLS with SmartPLS. The results show that Generation Z learning styles and digital financial literacy positively influence SRL, while SRL significantly affects economic literacy. AI utilization has no significant effect. SRL mediates the relationship between learning styles and digital financial literacy toward economic literacy.